A rare case of double orifice mitral valve with flail leaflet with embryological significance A case report - Kumar, Gattu Praveen; Shaffiuddin, Md (Bangladesh Journal of Medical Science, 2013)
Mitral valve having a double orifice opening into the left ventricle is an uncommon anomaly, In this case study we describe about a 25 years old female who came to cardiology outpatient block with exertional dysnea , the abnormality was suspected by a murmur ,further investigation Colour Doppler echocardiography showed congenital double-orifice mitral valve. This finding was confirmed by open heart surgery, and her mitral valve was successfully repaired. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17442 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 80-83